Protective Effects of Terpenes on the Cardiovascular System: Current Advances and Future Perspectives - M. Alves-Silva, Jorge; Zuzarte, Monica; Marques, Carla; Salgueiro, Ligia; Girao, Henrique (Current Medicinal Chemistry, 2016)
Background: Cardiovascular diseases (CVDs) are the leading cause of morbidity and mortality worldwide that seriously affect patient’s life quality and are responsible for huge economic and social burdens. It is widely accepted that a plant-based diet may reduce the risk of CVDs by attenuating several risk factors and/or modulating disease’s onset and progression. Plants are rich in secondary metabolites, being terpenes the most abundant and structurally diverse group. These compounds have shown broad therapeutic potential as antimicrobial, antiviral, anti-inflammatory and antitumor agents. Despite their popularity, scientific evidence on terpenes cardiovascular effects remains sparse, limiting their potential use as cardioprotective and/or cardiotherapeutic agents. Objective: Bearing in mind the lack of comprehensive and systematic studies, the present review aims to gather the knowledge and some of the most scientific evidence accumulated over the past years on the effect of terpenes in the cardiovascular field with focus on CVDs namely ischemic heart disease, heart failure, arrhythmias and hypertension. Method: Several popular search engines including PubMed, Science Direct, Scopus and Google Scholar were consulted. The bibliographic research focused primarily on English written papers published over the last 15 years. Results: A systematic and comprehensive update on the cardiovascular effects of terpenes is provided. Moreover, whenever known, the possible mechanisms of action underlying the cardiovascular effects are pointed out as well as an attempt to identify the most relevant structure- activity relationships of the different classes of terpenes. Conclusion: Overall, this review enables a better understanding of the cardiovascular effects of terpenes, thus paving the way towards future research in medicinal chemistry and rational drug design.
Keywords: cardioprotective